Smart method for determining evapotranspirations intented for water resources management in Cyprus : the case study of Polis Chrysochous - Christofi, Demetris A.D. (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The goal of his Dissertation thesis focuses on the phonological cycle of a specific crop, measuring Crop Height (CH) and Leaf Area Index (LAI) and attempts to correlate the with VI (Vegetation Indices) for deployment of a model contributing with the aid of remote sensed data manage hydrological needs via ETc, for a specific crop in a specific area . It will be a case study for the black eyed bean crop, the ground truth data will be collected in different area and time, later to be compared predicted values from developing satellite maps of LAI/CH. The phenological cycle of beans is in summertime , a suitable time window for monitoring the crop phenological stages during the period of composing my Dissertation thesis. Models involved with crop canopy factors will spatially enforce with remote sensed data and ground truth data that will verify and guide the remotely sensed data. The crop that is under study will provide the Vegetation indices from spectroradiometric measurements during the crops phenological stages. Crop canopy factors that we employ for the certain method, such as Leaf Area Index (LAI) and Crop Height (CH) are in the need of those indices. Results will be the combination of remotely sensed data providing the VI, ground truth data, plotted in a model abstracted from bibliography, providing LAI and CH predictions from remote sensed data, such as satellite image LAI/CH maps. Conclusively the target goal will be established providing the Leaf Area Index and Crop Height values for the crop under study (area of the Polis Chrysochou bay, Paphos), evaluation with LAI/CH maps, in different area and time (Mandria village area, Paphos), expecting the predicted LAI/CH values to match with the values of Ground measurements (Mandria village area, Paphos).
Keywords: Leaf Area Index; Crop Height; Polis Chrysochou bay; Mandria village area